ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA SEBAGAI STIMULASI COMPUTATIONAL THINKING PADA ANAK USIA 5-6 TAHUN - Ni Kadek Winda Adelia Pratiwi; I Komang Sesara Ariyana; I Putu Yoga Purandina (STKIP Subang, 2026)
This study aims to analyze the need for developing Canva-based interactive learning media as a stimulation of Computational Thinking in children aged 5–6 years. The needs analysis was conducted using three main instruments: (1) an observation sheet of teaching process activities, (2) structured interview instruments with the school principal and Group B teachers, and (3) a student needs analysis involving 24 Group B children at TK Kumara Satya Dharma. Observation results indicate that the learning process remains conventional and teacher-centered, with limited use of innovative learning models and varied digital media. Interview findings reveal that the primary obstacle is children's low interest and active engagement, while Smart TV use is limited to twice a week. Student needs analysis results show a very high level of acceptance of digital-based media: 100% of children enjoy digital games, interactive activities, musical elements, and collaborative learning via a large screen. These findings affirm the urgency of developing Canva-based interactive learning media that integrates digitalization, gamification, and a Computational Thinking approach appropriate to the developmental stage of children aged 5-6 years.